2017
DOI: 10.1111/padr.12072
|View full text |Cite
|
Sign up to set email alerts
|

Trading Youth for Citizenship? The Spousal Age Gap in Cross‐Border Marriages

Abstract: Prior studies concerning patterns of intermarriage among immigrants have primarily focused on how factors such as race/ethnicity, educational attainment, and country of origin shape the choice of a spouse. Moreover, they have focused on intermarriage patterns among immigrants who are already in the US. Using the 2010–2014 American Community Survey (ACS), we focus on immigrants who were not US citizens at the time of their marriage and highlight patterns of status exchange, specifically, the exchange of youth f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 42 publications
0
25
0
Order By: Relevance
“…A great segment of skilled youth desires for attaining immigration status in wealthier countries because of the worse socio-economic circumstances in their country of origin. This migration can either be a permanent or a semi-permanent change of residence [1]. Population movements are a fundamental human endeavour that has been happening since the beginning of mankind.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…A great segment of skilled youth desires for attaining immigration status in wealthier countries because of the worse socio-economic circumstances in their country of origin. This migration can either be a permanent or a semi-permanent change of residence [1]. Population movements are a fundamental human endeavour that has been happening since the beginning of mankind.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated a continuous growth in migration marriages of south-Asian women in western countries [5]. In South Asia, marriages with immigrants have been sparked by cultural pressures and a wish for better life opportunities [1]. Frequently, young women from developing countries marry older men to offer beauty, youth and domesticity with traditional gender roles and companionship [6].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Transnational processes and race are also tied to age-related partnering practices. Using the 2010-to-2014 ACS, Balistreri, Joyner, and Kao (2017) found that citizenship status was related to age gaps between partners, particularly for women. Immigrant women who married a U.S. citizen before or upon arrival had the largest age gaps between themselves and their husband, with smaller but still substantial gaps between immigrant women who married a U.S. citizen a year or more after arrival.…”
Section: Immigration National Origin and Racementioning
confidence: 99%